Eksistensialisme Tuhan Analisis Terhadap Pandangan Dan Kritik Jean-Paul Sartre - Joy Moses E Simbolon (Institut Agama Kristen Negeri Tarutung, 2020)
AbstractJean-Paul Sartre is an atheist philosophical figure that is well known for spreading his idea about existentialism. The purpose of this paper is to know what Jean-Paul Sartre knows about the existence of God. As for the purpose of this writing is to see Jean-Paul Sartre concept of God that said if God exist then humanity is nothing, man will be come it self if they nullify God himself. The method of the research ised is a literature research and descriptive method, which scientifically digs the flow and the core of Jean-Paul Sartre thoughts and what other factor that affects his thinking. The result of this research shows that for Sartre the existence of God only limits himself from freedom. With existence of God humans can’t be free to find their true identity. The real freedom according to Sartre is humans are willing to deny God’s existence in every aspect of their life. The implications tha we can get from Jean-Paul Sartre idea is we have to acknowledge that philosophical thinking can not be separated from the context of its era so we must be careful on understanding Sartre thoughts that stated that we become ourself when we deny the existence of God, that’s why as a human we must be willing to learn through education and our experiences with God, so we can develop meaning for ourself and those around us by prioritizing God. Because of that, we must be responsible with what we belief on reaching our own existence.Key Words: Exitensialism; Jean-Paul Sartre; God